A novel privacy-preserving federated genome-wide association study framework and its application in identifying potential risk variants in ankylosing spondylitis. Issue 3 (26th June 2020) - Wu, Xin; Zheng, Hao; Dou, Zuochao; Chen, Feng; Deng, Jieren; Chen, Xiang; Xu, Shengqian; Gao, Guanmin; Li, Mengmeng; Wang, Zhen; Xiao, Yuhui; Xie, Kang; et al.
Abstract: Genome-wide association studies (GWAS) have been widely used for identifying potential risk variants in various diseases. A statistically meaningful GWAS typically requires a large sample size to detect disease-associated single nucleotide polymorphisms (SNPs). However, a single institution usually only possesses a limited number of samples. Therefore, cross-institutional partnerships are required to increase sample size and statistical power. However, cross-institutional partnerships offer significant challenges, a major one being data privacy. For example, the privacy awareness of people, the impact of data privacy leakages and the privacy-related risks are becoming increasingly important, while there is no de-identification standard available to safeguard genomic data sharing. In this paper, we introduce a novel privacy-preserving federated GWAS framework (iPRIVATES). Equipped with privacy-preserving federated analysis, iPRIVATES enables multiple institutions to jointly perform GWAS analysis without leaking patient-level genotyping data. Only aggregated local statistics are exchanged within the study network. In addition, we evaluate the performance of iPRIVATES through both simulated data and a real-world application for identifying potential risk variants in ankylosing spondylitis (AS). The experimental results showed that the strongest signal of AS-associated SNPs reside mostly around the human leukocyte antigen (HLA) regions. The proposed iPRIVATES framework achieved equivalent results as traditional centralized implementation, demonstrating its great potential in driving collaborative genomic research for different diseases while preserving data privacy.